(untitled) (Journal of Medical & Health Sciences Review, 2025)
Marine ecosystems and coastal populations provide a variety of bioactive compounds that hold great promise for environmentally friendly drug development. This review emphasizes the importance of combining ethnopharmacological knowledge with marine resources to identify new therapeutics. By focusing on traditional healing practices, marine biodiversity, and cutting-edge biotechnology, it examines sustainable methods for bioprospecting and the ethical sharing of benefits with local communities. The article discusses the challenges of reconciling conservation efforts with drug discovery, the scalability of compounds derived from marine sources, and the existing policy frameworks. By merging interdisciplinary research, synthetic biology, and AI-based bioinformatics, marine bioprospecting can foster innovation while maintaining biodiversity and honoring the cultural traditions of coastal communities.